A series of N-trinitromethyl-substituted polynitro-pyrazoles: high-energy-density materials with positive oxygen balances. Issue 51 (22nd November 2022) - Ding, Lujia; Ge, Ruirong; Wang, Pengcheng; Li, Dongxue; Lin, Qiuhan; Lu, Ming; Xu, Yuangang
Abstract : A series of N -trinitromethyl-substituted polynitro-pyrazoles with positive oxygen balances were obtained by a simple and efficient synthesis, including N -acetomethylation followed by N -trinitromethylation. Abstract : An N -trinitromethyl strategy was employed for the synthesis of polynitro-pyrazole based high-energy-density compounds with great potential as energetic materials. The new compounds were characterized by 1 H and 13 C NMR, IR spectroscopy, elemental analysis, differential scanning calorimetry, and single-crystal X-ray diffraction. Compound 10 exhibits high energetic properties, has a positive oxygen balance (OB) of +2.1%, and an excellent specific impulse (272.4 s), making it a potential high-energy dense oxidizer to replace AP in solid rocket propellants. The nitration of 7 with HNO3 /H2 SO4 yielded the green primary explosive 12, which showed higher density, higher performance, better oxygen balance and lower sensitivities to those of currently used diazodinitrophenol. Compound 13 is a nitrogen and oxygen rich secondary explosive with a high OB (+5.0%), comparable energy ( D = 9030 m s −1 ; P = 35.6 GPa; η = 1.03) to HMX, and much lower mechanical sensitivity (IS = 12 J, FS = 240 N).